Understanding service-learning and community engagement : crossing boundaries through research - Hatcher, Julie A.; Bringle, Robert G. (Advances in service-learning research., 2011)
There is an increasing proliferation of service-learning courses in colleges and universities in the U.S. and internationally, and research in the field has seen significant growth in diverse geographic areas in the past decade. Membership organizations now exist to convene scholars and practitioners across the globe. Chapters in this volume are based on presentations given at the 2010 annual conference of the International Association for Research on Service Learning and Community Engagement held in Indianapolis, IN. The conference theme "International Perspectives: Crossing Boundaries through Research" was chosen to highlight ways in which research crosses all kinds of boundaries: disciplinary boundaries, cultural boundaries, and national boundaries.Although service-learning is valued as an active learning strategy across the globe, little is known about the ways that service-learning is similar or different in varied contexts. Understanding service-learning and community engagement from cross-cultural and crossdisciplinary perspectives will improve both research and practice. Together, these chapters represent the diversity, complexity, and creativity evident by scholars and practitioners in this field of study.